Investigation on the ohmic characteristic of Ni/Ti/4H-SiC - M. I. Idris; Z. A. F. M. Napiah; Marzaini Rashid; M. N. Shah Zainudin; Siti Amaniah Mohd Chachuli; M. A. Azam (Bulletin of Electrical Engineering and Informatics, 2021)
Ohmic contact is important for silicon carbide (SiC) devices such as Schottky diode, junction field effect transistor (JFET) and metal oxide transistor (MOSFET). The effect of post metallization annealing (PMA) on the ohmic characteristics of Ni/Ti/4H-SiC is investigated. The samples were annealed under different ambients of high vacuum, forming gas and N2 gas at 1050˚C for 3 minutes using rapid thermal process (RTP). Current-voltage (I-V) measurements taken for different distances of a transmission line model (TLM) structure have been utilized to extract the contact resistivity. The correlation between surface roughness and resistivity has been investigated. It was found that the involvement of nitrogen during the annealing process at 1050˚C was ineffective to reduce the contact resistivity. The resistivity is improved when the samples were annealed in forming gas (FG), (a mixture of H2+N2) environment, showing that the incorporation of H2 gas during the annealing process has produced a better result. On the other hand, high vacuum PMA was found to be effective to improve the ohmic characteristic with higher current level at lower voltage. Hence, the enhanced performance observed in high vacuum annealing samples is beneficial to get ohmic contact on Ni/Ti/4H-SiC for PMA process with a low thermal budget.